Migration Control, Forced Immobility and Violent Mobilization in West Africa - Cluster Project (Presenting The Cluster Projects, 2021)
Prof. Dr. Doevenspeck talks about his short term Cluster project: "Migration control, forced immobility and violent mobilization in the border triangle of Burkina Faso, Benin and Niger" that ran from Nov. 2019 to Oct 2020. Find more information here: https://www.africamultiple.uni-bayreuth.de/en/Research/1research-sections/mobilities/Migration-control_/index.html